ANALISIS PENGARUH RASIO-RASIO KEUANGAN TERHADAP RETURN SAHAM - Salsabillah, Shafira Rizki; Kharismar, Emir (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to empirically test and analyze the effect of current ratio, net profit margin, debt to asset ratio, inventory turnover, return on asset, earning per share, and price earning ratio on stock returns. The object of this research is company listed on the wholesale sub sector of the Indonesia Stock Exchange for 11 years, 2010-2020 period. The sample collection method used in this research is purposive sampling. There were 15 companies selected as the final sample that met the criteria. Data were analyzed using descriptive statistics and panel data regression techniques, with a common effect model to test hypotheses.The results of this study indicate that debt to asset ratio and return on asset have a positive effect on the stock returns. While current ratio, net profit margin, inventory turnover, earning per share, price earning ratio has no effect on stock returns.